Intronic variation at the CHD1‐Z gene in Black‐tailed Godwits Limosa limosa limosa: correlations with fitness components revisited. (18th June 2013) - Trimbos, Krijn B.; Kentie, Rosemarie; van der, Marco; Hooijmeijer, Jos C. E. W.; Poley, Carola; Musters, C. J. M.; de, Geert R.; Piersma, Theunis; Fuchs, Jerome
<x xml:space="preserve">Abstract</x> Recently, Schroeder et al. (2010, Ibis 152: 368–377) suggested that intronic variation in the CHD1‐Z gene of Black‐tailed Godwits breeding in southwest Friesland, The Netherlands, correlated with fitness components. Here we re‐examine this surprising result using an expanded dataset (2088 birds sampled from 2004 to 2010 vs. 284 birds from 2004 to 2007). We find that the presence of the Z* allele (9% of the birds) is not associated with breeding habitat type, egg size, adult survival, adult body mass or adult body condition. The results presented here, when used in synergy with the previously reported results by Schroeder et al., suggest that there might be a tendency towards female adults with the Z* allele laying earlier clutches than adult females without the Z* allele. The occurrence of the Z* allele was also associated with a higher chick body mass and return rate. Chicks with the Z* allele that had hatched early in the breeding season were heavier at birth than chicks without the Z* allele and chicks with the Z* allele that had hatched late. Collectively, the results suggest that variation in the CHD1‐Z gene may indeed have arisen as a byproduct of selection acting on females during the egg fase and on chicks during the rearing stages of the reproductive cycle.